2022
DOI: 10.2147/ijn.s371900
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Electrospun Nanofibers for Wound Healing Applications

Abstract: As a type of biological macromolecule, natural polysaccharides have been widely used in wound healing due to their low toxicity, good biocompatibility, degradability and reproducibility. Electrospinning is a versatile and simple technique for producing continuous nanoscale fibers from a variety of natural and synthetic polymers. The application of electrospun nanofibers as wound dressings has made great progress and they are considered one of the most effective wound dressings. This paper reviews the preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 149 publications
0
15
0
Order By: Relevance
“…Calcium ions help convert prothrombin to thrombin, accelerating the formation of blood clots and catalyzing many other coagulation-related reactions. It was observed that the highest coagulation rate was observed in polycaprolactone nanofibers with CaCO 3 content coated with β-chitosan [39].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium ions help convert prothrombin to thrombin, accelerating the formation of blood clots and catalyzing many other coagulation-related reactions. It was observed that the highest coagulation rate was observed in polycaprolactone nanofibers with CaCO 3 content coated with β-chitosan [39].…”
Section: Discussionmentioning
confidence: 99%
“…Starch is a carbohydrate type of polymer that is explored in different biomedical applications, such as wound healing due to its biocompatibility, availability, and low cost. It has also been used for cell adhesion, proliferation, and regeneration, hence starch-based scaffolds have great therapeutic significance in wound healing applications [ 64 , 65 ]. Some undesirable properties of starch, such as its sensitivity to moisture and mechanical strength negatively, impact its application in tissue engineering, however, polyvinyl alcohol can be used as a plasticizer in its electrospinning process.…”
Section: Polymers Used In the Fabrication Of Nanofibrous Scaffoldsmentioning
confidence: 99%
“…At the same time, there are still large pores in these traditional dressings, which cannot avoid the contact between bacteria in the air and the wound ( Simões et al, 2018 ; Obagi et al, 2019 ). With the development of time, modern dressings represented by hydrogels, fiber dressings, foam dressings and film dressings are gradually applied in clinical practice ( Walker et al, 2017 ; Liang et al, 2021a ; Tan et al, 2022 ). These dressings can create a moist surface environment for the wound and prevent bacteria from passing through the dressing and entering the wound while ensuring gas exchange ( Francesko et al, 2018 ).…”
Section: Characteristics Of Wound Dressing In Skin Wound Healingmentioning
confidence: 99%